The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1155/2020/6471837
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Geological Strength Index (GSI) as an Empirical Classification and Rock Mass Property Estimation Tool: Origination, Modifications, Applications, and Limitations

Abstract: The geological strength index (GSI) is one of the most exceptional rock mass classification system which is used to evaluate very weak and highly jointed rock mass by different approaches and related to rock mass geomechanical properties including generalized Hoek & Brown constants, deformation modulus, strength properties, and Poisson’s ratio for an appropriate design of tunnels, caverns, and other engineering structures. The distinctiveness of this system over the rock mass rating (RMR), Q-system, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 65 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…An important input parameter of the Hoek-Brown failure criterion is the geological strength index, developed to describe the rock structure and fracture surface conditions in a rock mass. GSI is determined by visual inspection of the mass, outcropped surfaces of mine workings and pieces of rock cores [33]. Using GSI, the mechanical behavior of the rock mass can be accurately assessed for both very poor and very good quality rocks [33].…”
Section: Figure 1 General Diagram For Gsi Assessments Based On Geolog...mentioning
confidence: 99%
“…An important input parameter of the Hoek-Brown failure criterion is the geological strength index, developed to describe the rock structure and fracture surface conditions in a rock mass. GSI is determined by visual inspection of the mass, outcropped surfaces of mine workings and pieces of rock cores [33]. Using GSI, the mechanical behavior of the rock mass can be accurately assessed for both very poor and very good quality rocks [33].…”
Section: Figure 1 General Diagram For Gsi Assessments Based On Geolog...mentioning
confidence: 99%
“…The popularity of the early GSI was to build a bridge of communication between the experimentally measured strength parameters of rock masses and the deformation characteristics of rock outcrops [30]. It has been shown that the GSI chart can quantify the degree of tectonic deformation as a quantitative classification indicator, which gives measurability to descriptive language that relies on visual methods to obtain words with unclear meanings, such as bulky, well-interlaced, partially disturbed, etc.…”
Section: Construction Of Geological Strength Index (Gsi) With Type-2 ...mentioning
confidence: 99%
“…The equivalent angles of friction and cohesive strengths are given by (Hussian et al, 2020) as follows:…”
Section: Practical Estimates Of Rock Mass Parametersmentioning
confidence: 99%